NATIONAL SYSTEM'S OF BIOLOGICAL SAFETY CREATION AS PRIORITY DIRECTION OF NEW TYPES OF FOOD STUFFS' STATE REGULATION - Gribko O.V. (Pressing Problems of Public Administration, 2015)
The issue is devoted to theoretical substantiation of the government control mechanisms forthe food market, transformation of which is caused by emergence of new types of food stuffs(NTFS), also it analyses the provisions of ensuring biological safety based on Cartagena protocol(2000) ratified by Verhovna Rada of Ukraine.